Copper tolerant yeasts isolated from polluted area of Argentina - Villegas, Liliana Beatriz (2005)
Eleven yeasts were isolated from wastewater sediment samples collected from a copper filter mine plant, located in the province of Tucumán, Argentina, and tested for their heavy metal tolerance. Two isolates were selected based on their multiple tolerance to different heavy metals and their copper biosorption capacity was studied. Analysis of the 26S rDNA D1/D2 domain sequences indicates that isolate RCL‐3 showed similarity with Candida sp. and RCL‐11 with Rhodotorula mucilaginosa . Growth performance and copper toxicity of both yeasts were evaluated using YNB‐glucose medium supplemented with 0.1, 0.2, 0.5 and 1 mM of Cu2+ solutions. Candida sp. RCL‐3 was able to grow up to 7 mg ml–1 biomass in the presence of either 0.1 or 0.2 mM Cu2+, and at 0.5 mM Cu2+ growth reached 5.5 mg ml–1. R. mucilaginosa RCL‐11 reached 8 mg ml–1 in the presence of 0.1 mM Cu2+, and values of 6.5 and 5.5 mg ml–1 biomass were obtained at 0.2 and 0.5 mM Cu2+, respectively. Copper accumulation profiles were different: the metal was librated from the intact cells by Candida sp. whereas R. mucilaginosa did not show release from the cells indicating intracellular storage. Specific biosorption of copper by both isolated yeasts showed increase with the initial copper supplied with the medium (up to 11.5 and 8.0 mg Cu g–1 biomass for Candida sp. and R. mucilaginosa , respectively). However, specific biosorption decreased with time.